Phase memory of the three-level system in the presence of external spatially inhomogeneous electric fields - E.I. Nizamova; L.A. Nefediev; G.A. Gilmanova (Учёные записки Казанского университета: Серия Физико-математические науки)
The increasing interest in the study of the interaction of several resonant fields with multilevel quantum systems is due to a wide range of possible applications of various effects observed in the multi-frequency excitation of quantum objects. Among them, we can note color echo holography, information compression in three-level environments, copying of quantum information, and multi-level quantum gates that perform logical operations. In addition, the recording and reproduction of echo holograms in multi-level systems leads to the possibility, along with logical operations, to perform a change in the real-time scale and the sequence of events in the echo-hologram response, the data on which were embedded into the temporal structure of the object laser pulse. The formation of optical transient processes in multilevel systems occurs when the short laser pulses separated in time and resonant of different frequency transitions at the substance have an effect on the system, so that their interaction with each other becomes possible only through the medium and only if the medium has a sufficiently long phase memory. In this situation, each laser pulse transmits information about its wave characteristics to the medium, and this information is retained here until the arrival of the next laser pulses. The formation of optical transient processes in a multilevel system in a solid depends essentially on the degree of correlation of the inhomogeneous broadening on different frequency transitions and different time intervals, in connection with the possible destruction of the reversible phase memory of the system due to a partial mutual fixation energies of transitions. The influence of external spatially inhomogeneous electric fields on the resonant medium can lead to an additional artificially created inhomogeneous broadening. In this case, it is possible to control the phase memory of the system by changing the parameters of external spatially inhomogeneous electric fields, and the most pronounced effect on phase memory is the case of laser excitation of narrow frequency regions of inhomogeneously broadened lines of the resonance transitions. Moreover, the artificially created inhomogeneous broadening by external spatially inhomogeneous electric fields due to the Stark effect can be comparable with the spread of frequencies due to a partial mutual fixation of the transition energies, which leads to a partial restoration of the coherence of the multilevel system. This effect can lead to an increase in the intensity of the response of the stimulated photon echo (SPE) in the three-level system, which is the opposite effect of photon echo locking.